2014
DOI: 10.1002/bdrc.21078
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest development in fetal alcohol syndrome

Abstract: Fetal alcohol spectrum disorder (FASD) is a leading cause of neurodevelopmental disability. Some affected individuals possess distinctive craniofacial deficits, but many more lack overt facial changes. An understanding of the mechanisms underlying these deficits would inform their diagnostic utility. Our understanding of these mechanisms is challenged because ethanol lacks a single receptor when redirecting cellular activity. This review summarizes our current understanding of how ethanol alters neural crest d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
102
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 83 publications
2
102
0
1
Order By: Relevance
“…29,30 Furthermore, regarding the direct role of genes involved in alcohol metabolism in modifying risk, evidence from laboratory studies using ethanolsensitive and ethanol-resistant chickens, mice, and zebra fish provides insight into the multifactorial genetics of ethanol-mediated cell signaling disruption and neural crest apoptosis. 31 We observed that children of mothers who reported feeling the effects of alcohol quickly or very quickly exhibited larger craniofacial differences in most exposure groups. We hypothesize that this rate of feeling the effects of alcohol reflects genetically determined variation in alcohol metabolism.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…29,30 Furthermore, regarding the direct role of genes involved in alcohol metabolism in modifying risk, evidence from laboratory studies using ethanolsensitive and ethanol-resistant chickens, mice, and zebra fish provides insight into the multifactorial genetics of ethanol-mediated cell signaling disruption and neural crest apoptosis. 31 We observed that children of mothers who reported feeling the effects of alcohol quickly or very quickly exhibited larger craniofacial differences in most exposure groups. We hypothesize that this rate of feeling the effects of alcohol reflects genetically determined variation in alcohol metabolism.…”
Section: Discussionmentioning
confidence: 68%
“…31 Correlative face-brain phenotypes have been described in human and animal studies, suggesting that the type and severity of brain abnormality may be predicted in part by hypoplasia of the midface, 28,32 and that the classic facial features of FASD (short palpebral fissure, smooth philtrum, and thin upper lip) may assist in identifying children at risk of developing neurobehavioral deficits. 5 Given that cognitive outcomes for the children in our study have not yet been examined in this context, it is as yet unknown if the craniofacial differences found are of diagnostic or predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we and others have reported that alcohol causes the apoptotic death of an early neuroprogenitor population called the neural crest [68]. Disruptions in neural crest development contribute to a characteristic craniofacial dysmorphology that can be diagnostic for some individuals who exhibit FASD morphological characteristics [9,10]. Using an established chick embryo model of alcohol exposure, we showed that alcohol causes craniofacial structural changes consistent with those of the human disorder [6,9].…”
Section: Introductionmentioning
confidence: 73%
“…[21][22][23]109,110 Studies linking animal models with human patients will be vital to advancing our understanding of FASD and to identify potential therapeutic approaches to overcome its catastrophic effects. Zebrafish is particularly well suited for studying the pathology of FASD because of its high fecundity, external fertilization, embryo transparency, rapid development time, and genetic tractability.…”
Section: Discussionmentioning
confidence: 99%